Analysis of Life Cycle Cost and Public-Private Partnership in the Development of Walini City as Technology Park - Berawi, Mohammed Ali; Nabila, Asifa; Gunawan, Gunawan; Miraj, Perdana; Abdul-Rahman, Hamzah; Berawi, Abdur Rohim Boy (Faculty of Engineering, Universitas Indonesia, 2018)
Walini is an area with potential for development into a technology park based on its population and economic growth. This paper aims to analyse the investment feasibility of the development of Walini Technology Park and its optimum funding scheme. The life-cycle analysis approach is used to evaluate operation and maintenance (OM) costs and the system dynamics technique to generate revenue. The study will focus on examining scenario alternatives to determine an optimum public-private partnership (PPP) scheme. The results show that development of Walini would require an investment cost of 151 trillion rupiahs (US$ 9.97 billion) and OM costs of 353 trillion rupiahs (US$ 23.3 billion). The development would generate a revenue of 75 billion dollars, with a 35-year concession period. 42 scenarios were considered in order to obtain that with optimal Internal Rate of Return (IRR) values. The optimal IRR score is 15.57%, with a private share of around 49.89% of the initial costs, 60.08% of operational and maintenance costs, and 80.06% of revenue.